First record of proechimys pattoni da silva, 1998 (Rodentia, echimyidae) in northwestern Bolivia - Sánchez-Vendizú P. (2018)
Proechimys pattoni da Silva, 1998 is one of the 3 small-bodied species of Proechimys and its geographic range is only known in western Brazil and eastern and southern Peru. However, based on morphological and molecular analyses, we report P. pattoni from the lowland forest of Bolivia (Pando: Rio Madre de Dios, near San Rosa). This is the first report of P. pattoni in Bolivia and extends its distributional range 315 km to the southeast in the Amazon biogeographic region of Bolivia, representing the southeastern most record. Furthermore, we document the karyotype (2n = 40 / FN = 56) and morphological variation in diagnostic characters. © Sánchez-Vendizú et al.